Examining Zomi refugees psychological adaptation with the psychological antecedents of refugee integration model - Tai, L.L.; Guerra, R.; Bierwiaczonek, K. (2022)
The current research examined the psychological factors associated with refugee adaptation, focusing on Zomi refugees in Malaysia. Specifically, building on the psychological antecedents of refugee integration (PARI) model (Echterhoff et al., 2020), this study considered the role of loss of control, perception of forcedness and related perils for refugee’s subjective well-being for Zomi refugees as compared with non-Zomi refugees. Data were collected through an online survey involving Zomi refugees (N = 258) and non-Zomi refugees (N = 158). Using multigroup structural equations modelling, we found that the role of our variables of interest differed in the two groups. For non-Zomi refugees, loss of control was positively associated with the perception of forcedness and negatively linked with subjective well-being. For Zomi refugees, loss of control was negatively correlated with the perception of forcedness and not associated with subjective well-being. The indirect effect of perception of forcedness and related perils with subjective well-being via loss of control was not significant in either group. We propose that Zomi refugees have a different conception of control compared to non-Zomi refugees, and we suggest that specific cultural and contextual factors influence these differences. The limitations, practical implications, and future research were discussed. The current research examined the psychological factors associated with refugee adaptation, focusing on Zomi refugees in Malaysia. Specifically, building on the psychological antecedents of refugee integration (PARI) model (Echterhoff et al., 2020), this study considered the role of loss of control, perception of forcedness and related perils for refugee’s subjective well-being for Zomi refugees as compared with non-Zomi refugees. Data were collected through an online survey involving Zomi refugees (N = 258) and non-Zomi refugees (N = 158). Using multigroup structural equations modelling, we found that the role of our variables of interest differed in the two groups. For non-Zomi refugees, loss of control was positively associated with the perception of forcedness and negatively linked with subjective well-being. For Zomi refugees, loss of control was negatively correlated with the perception of forcedness and not associated with subjective well-being. The indirect effect of perception of forcedness and related perils with subjective well-being via loss of control was not significant in either group. We propose that Zomi refugees have a different conception of control compared to non-Zomi refugees, and we suggest that specific cultural and contextual factors influence these differences. The limitations, practical implications, and future research were discussed. Keywords: Zomi, PARI, psychological adaptation, subjective well-being, perception of forcedness, related perils, loss of control, refugees.